2016
DOI: 10.1038/srep37675
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Validity of the Phonon Gas Model in Amorphous Materials

Abstract: The idea of treating phonon transport as equivalent to transport through a gas of particles is termed the phonon gas model (PGM), and it has been used almost ubiquitously to try and understand heat conduction in all solids. However, most of the modes in disordered materials do not propagate and thus may contribute to heat conduction in a fundamentally different way than is described by the PGM. From a practical perspective, the problem with trying to apply the PGM to amorphous materials is the fact that one ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 44 publications
2
54
1
Order By: Relevance
“…Specifically, by calculating the density of states of the propagating vibrations with a Debye model, we estimate that about 24% of all modes are propagating waves. Our observation is consistent with prior calculations of dynamical structure factor [6,19] but is inconsistent with prior conclusions that propagons have frequencies less than 2-3 THz in amorphous silicon [3,[5][6][7]17,20].…”
Section: A Dynamic Structure Factorsupporting
confidence: 45%
“…Specifically, by calculating the density of states of the propagating vibrations with a Debye model, we estimate that about 24% of all modes are propagating waves. Our observation is consistent with prior calculations of dynamical structure factor [6,19] but is inconsistent with prior conclusions that propagons have frequencies less than 2-3 THz in amorphous silicon [3,[5][6][7]17,20].…”
Section: A Dynamic Structure Factorsupporting
confidence: 45%
“…Conceptually, propagons largely resemble the usual definition of phonons and can carry energy with a speed governed by the group velocity. Thus, propagons can usually be treated as long wavelength phonons with the PGM, but this model is not applicable to diffusons based on a detailed study using normal mode lifetime analysis . Using nonequilibrium MD simulations, He et al reported that propagons with an MFP on the order of micrometer contribute roughly half the total thermal conductivity in amorphous silicon .…”
Section: Contributions From Different Heat Carriersmentioning
confidence: 99%
“…Various simulation and experimental methodologies have been developed in the study of the physical characteristics of thermal transport in amorphous materials. Molecular dynamics (MD) simulation is a commonly used computational tool . In MD simulation, the positions and velocities of all atoms evolve following Newton's laws of motion.…”
Section: Introductionmentioning
confidence: 99%
“…We then used a cubic supercell of a 2 × 2 × 2 conventional unit cell, which consists of 64 atoms in total, to compute the various terms in Eq. (9).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Each step in vibrational mode energy is then thought of as a quasi-particle termed a phonon, and the theory describing their transport is known as the phonon gas model (PGM). [1][2][3][4][5][6][7][8][9] The PGM was largely born out of the types of vibrations that would exist in an infinitely large, pure, homogeneous crystal (IPHC). In such a system, one can solve the equations of motion in the harmonic limit and find that all solutions correspond to plane wave modulated vibrations, as a result of the periodicity.…”
Section: Introductionmentioning
confidence: 99%